Consensus Statements on the Approach to COVID-19 Vaccine Allergy Safety in Hong Kong - Chiang, Valerie; Leung, Agnes S. Y.; Au, Elaine Y. L.; Ho, Marco H. K.; Lee, Tak Hong; Wu, Adrian Y. Y.; Wong, Gary W. K.; Li, Philip H. (Frontiers in Allergy, 2021)
Background: Mass coronavirus disease 2019 (COVID-19) vaccination to achieve herd immunity is an effective means to mitigate the current COVID-19 pandemic. Reports of COVID-19 vaccine-associated allergic reactions and lack of clear local guidance are contributing factors leading to a low vaccine acceptance rate in the community. A task force of experts from the Hong Kong Institute of Allergy (HKIA) has been formed to address current needs. Objective: To formulate a set of consensus statements (CS) on COVID-19 vaccine allergy safety (VAS) in Hong Kong. Methods: A nominated task force of experts managing patients with drug and vaccine allergies in Hong Kong formulated the CS by the Delphi method. An agreement was a priori defined as ≥80% consensus. Results: A total of 11 statements met the criteria for consensus with good overall agreement among task force members, including seven statements on pre-vaccination recommendations and four statements on vaccination and post-vaccination guidance. Individuals with a history of suspected allergic reaction to prior COVID-19 vaccination should not receive further COVID-19 vaccination, and other groups at risk of COVID-19 vaccine-associated allergic reactions have been identified. The importance of pre-vaccination and post-vaccination assessment by frontline healthcare workers and evaluation by allergists are highlighted. Conclusion: The CS provides pragmatic and timely guidance for local frontline healthcare providers on decisions regarding COVID-19 VAS.